RANCANG BANGUN GAME ADVENTURE BAPER (ABAH SUPER) MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Saepul Mahri; Dadan Zaliluddin (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Culture is formed from many complex elements, including religious, political, customary, linguistic, tool-related, clothing, architectural, and artistic systems. According to the theory proposed by E.B. Taylor, culture is a comprehensive complex that encompasses knowledge, beliefs, art, morality, laws, customs, as well as human learning capabilities and other habits as members of society. Meanwhile, according to Koentjaraningrat, culture is a system of ideas, feelings, actions, and works produced by humans in their communal life. The term "game" refers to "permainan" in the English language. According to Clark C. Abt, a game is an activity involving player decisions, aiming to achieve goals that are "constrained by a specific context" (for example, limited by rules). In a game, there is usually a background that serves as the setting for the game, and for this game development, the author chose the case study of the forest in Sukamenak Village where monkeys frequently come down to the road to search for food, making it a potential tourist attraction and a source of income for the village. However, the lack of awareness about the forest and its history and culture in Sukamenak Village is a challenge.